Expression differences in Aphidius ervi (Hymenoptera: Braconidae) females reared on different aphid host species - Gabriel I. Ballesteros; Jürgen Gadau; Fabrice Legeai; Angelica Gonzalez-Gonzalez; Blas Lavandero; Jean-Christophe Simon; Christian C. Figueroa (PeerJ, 2017)
The molecular mechanisms that allow generalist parasitoids to exploit many, often very distinct hosts are practically unknown. The wasp Aphidius ervi, a generalist koinobiont parasitoid of aphids, was introduced from Europe into Chile in the late 1970s to control agriculturally important aphid species. A recent study showed significant differences in host preference and host acceptance (infectivity) depending on the host A. ervi were reared on. In contrast, no genetic differentiation between A. ervi populations parasitizing different aphid species and aphids of the same species reared on different host plants was found in Chile. Additionally, the same study did not find any fitness effects in A. ervi if offspring were reared on a different host as their mothers. Here, we determined the effect of aphid host species (Sitobion avenae versus Acyrthosiphon pisum reared on two different host plants alfalfa and pea) on the transcriptome of adult A. ervi females. We found a large number of differentially expressed genes (between host species: head: 2,765; body: 1,216; within the same aphid host species reared on different host plants: alfalfa versus pea: head 593; body 222). As expected, the transcriptomes from parasitoids reared on the same host species (pea aphid) but originating from different host plants (pea versus alfalfa) were more similar to each other than the transcriptomes of parasitoids reared on a different aphid host and host plant (head: 648 and 1,524 transcripts; body: 566 and 428 transcripts). We found several differentially expressed odorant binding proteins and olfactory receptor proteins in particular, when we compared parasitoids from different host species. Additionally, we found differentially expressed genes involved in neuronal growth and development as well as signaling pathways. These results point towards a significant rewiring of the transcriptome of A. ervi depending on aphid-plant complex where parasitoids develop, even if different biotypes of a certain aphid host species (A. pisum) are reared on the same host plant. This difference seems to persist even after the different wasp populations were reared on the same aphid host in the laboratory for more than 50 generations. This indicates that either the imprinting process is very persistent or there is enough genetic/allelic variation between A. ervi populations. The role of distinct molecular mechanisms is discussed in terms of the formation of host fidelity.